Investigation on Electron Energy Distribution in Multi- Component Plasma in Nuclear Fuel Rod Gap - Fereshteh Golian; Ali Pazirandeh; Saeid Mohammadi (مجله علوم و فنون هسته‌ای, 2014)
The electron energy distribution function in fuel rod gap of Busheher’s VVER-1000 nuclear reactor was investigated using the Fokker-Planck equation. In this regard, the Fokker-Planck equation was solved by using the Runge-Kutta numerical method, and the non-equilibrium behavior of electrons passing through the gap, as an absorbing medium, was evaluated and analyzed. The programming language C++ was employed to acquire high accuracy. Besides, by utilizing the Monte Carlo GEANT4 code, the fission reaction in the fuel rod was simulated and the energy distribution of electron was calculated. Furthermore, it was found that most of the electrons are essentially thermal in the fuel rod gap and the electrons energy distribution is far from Maxwellian distribution. Also, the krypton effect on the energy distribution of electron was investigated. One of the outstanding points that should be mentioned here is that the krypton has no significant effect on the energy distribution function of electrons in the fuel rod gap.